Penerapan Metode MAUT Dalam Rekrutmen Kepala Gudang di Perusahaan Dengan Pembobotan ROC - Mohammad Aldinugroho Abdullah; Rima Tamara Aldisa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Recruitment is a process that must be passed by someone by following the stages determined by the company to fill the position that is being opened, namely the head of the warehouse. someone who is in charge of overseeing all work related to warehouses to fulfill the wishes or targets of a company and is able to control and ensure the availability of goods according to the market is called the head of the warehouse. The recruitment process to become the head of the warehouse is certainly not easy, usually the Human Resource Development (HRD) has set several requirements that have been received from the management. Because the many requirements to become a warehouse head can make candidates think and reconsider applying for the position of warehouse head, making it difficult for Human Resource Development (HRD) to find suitable candidates. In recruiting warehouse heads, an information system is needed that can make the screening process for warehouse head candidates more effective, namely using a decision support system (SPK) by applying the MAUT method with ROC weighting with the best alternative decision results, namely alternative A2 on behalf of "Dindin Samsudin" with a value of Ui = 0.761 which is accepted as the head of the warehouse.